Navigating academic and sociocultural challenges: Indonesian EFL pre-service teachers experience in an ESL teaching practicum - Irfan Rifai; Vira Ayu Kartika; Syazliyati Ibrahim (Universitas PGRI Madiun, 2025)
This paper reports a qualitative case study examining Indonesian EFL pre-service teacher trainees experiences of an international teaching practicum at upper secondary schools in the Philippines. Drawing on narrative accounts from three teacher trainees and employing thematic analysis, the findings reveal two prominent themes related to the challenges encountered during the teaching practicum in an ESL context: academic-related and sociocultural aspects. The findings indicate that differences in the status of English and accent use significantly affected the trainees emotions and perceptions. In addition, differences in the focus of the curriculum and syllabus, as well as the higher level of instructional materials used in the host schools, required the trainees to make greater efforts to learn and adapt. Regarding sociocultural aspects, the most salient challenges were related to unfamiliar cultural practices that the trainees needed to address with professional sensitivity. This study suggests that international teaching practicum involves not only academic demands but also broader social and cultural dimensions that require teacher trainees to be anticipative and culturally responsive. Therefore, teaching practicum programs should provide greater exposure to intercultural awareness and the development of global teaching skills.